Motivation management of tourist services consumer - M. A. Zhukova (Вестник университета)
The motives, that guide travelers when choosing a tourist product, have been considered. The motives have been divided into three types, depending on the degree of interdependence of primary and secondary motives of tourists. The trends, that have a significant impact on the formation of consumer and hotel consumer motivations, have been identified. Based on the analysis of various theoretical concepts of tourist motivation (analytical, hierarchical and complex), it has been proposed to group tourist motivations into the following groups: physical motivations for recreation, cultural and natural-climatic motivations, social motivations, motivations for changes in the type of activity, motivations of status and prestige, and motivations for entertainment . A list of types of recreation has been formulated, and their interrelation with the types of tourism, that travelers enjoy the most demand has been shown.